Improving the Family Caregiver’s Knowledge about Diet Diabetes Management through WhatsApp online Health Educations - Rinco Siregar; Agnes Silvina Marbun; Lasma Rina Sinurat (Puslitbang Sinergis Asa Professional, 2023)
Information about diet management of Type 2 Diabetes Mellitus (T2DM) is very important for family caregivers caring for elderly with T2DM. Family caregivers should have a good knowledge of how to manage dietary restriction for elderly with T2DM. The purpose of the study was to determine the effect of the online health education about diet diabetes management through WhatsApp media on family caregiver’s knowledge at Rantang Public Health Center (PHC), Medan. The research design used in this study was a quasi-experimental study pretest and posttest only one group. The samples were twenty-two family caregivers caring for elderly with T2DM at home and were selected using a purposive sampling. Online Health Education about diet diabetes management of elderly with T2DM through WhatsApp was delivered to family caregiver for four weeks. Family caregiver’s knowledge was measured by Knowledge of Diabetic Diet Questionnaire (KDDQ-I). The results of this study found that the mean score of knowledge before receiving the online health education was 11.95, and after receiving the online health education the mean score of knowledge was 18.18. The Wilcoxon test found a difference in mean score of knowledge before and after receiving online health education through WhatsApp (P < 0.05). The family caregiver’s knowledge was increasing 6.23 points through WhatsApp online education. It can be concluded that using WhatsApp media for health education is proven to increase family caregivers' knowledge about DM dietary management. WhatsApp can be used by health workers as a media for health education.